Nationalist in the Viet Nam Wars : Memoirs of a Victim Turned Soldier - Nguyễn, Công Luận, 1937- (Book collections on Project MUSE., 2012)
"This extraordinary memoir tells the story of one man's experience of the wars of Viet Nam from the time he was old enough to be aware of war in the 1940s until his departure for America 15 years after the collapse of South Viet Nam in 1975. Nguyen Cong Luan was, by his account, "just a nobody." Born and raised in small villages near Ha Noi, he and his family knew war at the hands of the Japanese, the French, and the Viet Minh. Living with wars of conquest, colonialism, and revolution led him finally to move south and take up the cause of the Republic of Viet Nam, changing from a life of victimhood to that of a soldier. His stories of village life in the north are every bit as compelling as his stories of combat and the tragedies of war. "I've done nothing important," Luan writes. "Neither have I strived to make myself a hero." Yet this honest and impassioned account of life in Viet Nam from World War II through the early years of the unified Communist government is filled with the everyday heroism of the common people of his generation. Luan's portrayal of the French colonial occupation, of the corruption and brutality of the Communist system, of the systemic weakness and corruption of the South Vietnamese government, and his "warts and all" portrayal of the U.S. military and the government's handling of the war may disturb readers of various points of view. Most will agree that this memoir provides a unique and important perspective on life in Viet Nam during the years of conflict that brought so much suffering to Luan and his fellow Vietnamese."--Publisher's description.